Structural and biophysical characterisations of MeCP2 MBD mutants that correlate with Rett syndrome - Chia, Jyh Yea (2016)
Methyl-CpG binding protein (MBD) family consists of Methyl-CpG Binding Protein 2 (MeCP2), Methyl-CpG Binding Domain Protein 1 (MBD1), MBD2, MBD3 and MBD4 where MeCP2 is the prototype of the family. MeCP2 contains several domains: (a) a methyl-CpG binding domain (MBD), (b) a transcriptional repression domain (TRD), (c) two AT hooks and (d) a nuclear localisation signal (NLS). MeCP2 binds to methylated DNA and represses the transcription of the associated genes. Mutations in MECP2 lead to Rett syndrome (RTT), which is characterised by progressive neuro-developmental disorder in early childhood of females. Previous studies revealed that most RTT missense mutations alter the protein conformation and subsequently interferes the methyl-CpG recognition. To understand how the structural changes contribute to RTT, the 3-dimensional structure of these mutants need to be elucidated. Therefore, it is of interest to study the structure of RTT related MBD in complex with methylated DNA using X-ray crystallography and characterised the DNA-protein binding with some biophysical assays. Since more than 50% of the missense mutations occur within the MBD domain. Out of the 8 hot RTT spots within this domain, RTT mutants D97E, A140V, Y141C, P152R and D156E were included in this study. In band shift assay, wild-type MBD complexed with DNA was significantly shifted compared to A140V and D97E while other mutants were not significantly shifted. In SPR, wild-type MBD showed the highest affinity towards the DNA followed by A140V (KD: 0.28 μM). Circular dichrosim (CD) analysis revealed that the secondary structures of A140V, Y141C, P152R and D156E are highly similar to wild-type MBD (14.7 % -helix, 25.2 % -strand, and 60.1 % turns and unordered) except for D97E which showed 31 % -helix, 6.5 % -strand, 62.5 % turns and unordered. The complex of MBD140V with methylated DNA was crystallised and diffracted X-ray to 2.2 Å resolution. The co-crystal belongs to monoclinic space group C2, with unit cell parameters of a=78.66 Å, b=53.49 Å, c=62.78 Å, ==90 ° and β=132.47 °. X-ray analysis revealed that the MBD domain was not altered by mutation of Ala-140 to Val (A140V). However, additional water molecules were identified at the DNA-protein contact interface and around the DNA molecule. A narrow minor groove of A/T run was observed as a result of additional bifurcated hydrogen bonds and vertical stacking of bases results from high degree of propeller twist and heavy purine-purine stacking. Two hydration spines were observed running down the wall of the minor groove. Each hydration spine is well arranged into two shells adopting a zig-zag arrangement. Hence, this finding provides insights for the DNA geometry where the A/T run is geometrically stabilized by extensive water network and is independent of the flanking nucleotide sequence, DNA methylation and the bound MBD domain. The finding explores characteristics of the methylated DNA containing A/T run, which provide the nucleotide sequence preferences to MeCP2. In general, these additional molecular details could provide fundamental knowledge in RTT therapeutic approaches.